2022
DOI: 10.3389/fonc.2021.759652
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Favorable Response and Manageable Toxicity to the Combination of Camrelizumab, Oxaliplatin, and Oral S-1 in a Patient With Advanced Epstein–Barr Virus-Associated Gastric Cancer

Abstract: Some pertinent studies have demonstrated that Epstein–Barr virus-associated gastric cancer (EBVaGC) patients showed a favorable clinical outcome to immunotherapy and Epstein–Barr virus (EBV)-positive status might be a potential biomarker for immunotherapy in gastric cancer (GC). However, knowledge of given exposure to EBVaGC to the first-line immunotherapy is largely inadequate. Moreover, whether camrelizumab can be as effective as other PD-1 inhibitors in the treatment of advanced EBVaGC has not been reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
3
3
2
Order By: Relevance
“…Besides, the PFS of our case (beyond 20 months) was more prominent, and it could be translated into long-term survival. Similar results had been reported ( 10 ), which may attribute to the unique characteristics of EBV-related cancers. The present case indicated EBV was a strong biomarker for the immunotherapy of GC.…”
Section: Discussionsupporting
confidence: 90%
“…Besides, the PFS of our case (beyond 20 months) was more prominent, and it could be translated into long-term survival. Similar results had been reported ( 10 ), which may attribute to the unique characteristics of EBV-related cancers. The present case indicated EBV was a strong biomarker for the immunotherapy of GC.…”
Section: Discussionsupporting
confidence: 90%
“…After comparing and summarizing several previous studies, immunotherapy plus chemotherapy showed better treatment effects for gastric cancer patients ( 22 ). At the same time, immunotherapy plus chemotherapy can achieve a good prognosis of gastric cancer patients while reducing toxic side effects, which has also been reported in previous case reports ( 23 25 ). In our case, the patient suffered from gastrointestinal and myelosuppressive side effects due to intravenous oxaliplatin.…”
Section: Discussionsupporting
confidence: 81%
“…However, the expected tumor regression was not attained. Compared with a previous case of EBV-associated gastric cancer, the present case had a less abundant TIME, such as CD8 + T cell density (10.59% vs. 2.87%) (Lv et al, 2022). Compared with EBVa ICC, EBVa LEL-ICC had significantly increased densities of CD8 + T cells (Huang et al, 2021).…”
Section: Discussioncontrasting
confidence: 56%
“…EBV-associated cancer is significantly responsive to immunotherapy. This response has been documented in previous cases of stomach, lung, liver, and bile duct cancer (Jiang et al, 2015;Xie et al, 2020;Huang et al, 2021;Lv et al, 2022;Zhu et al, 2022). Its sensitivity to immunotherapy was related to the upregulated expression of programmed death ligand 1 (PD-L1) (Wang et al, 2022).…”
Section: Introductionsupporting
confidence: 66%